Proteomic Profiling and Epitope Analysis of the Complex α-, γ-, and ω-Gliadin Families in a Commercial Bread Wheat - Cho, Kyoungwon; Beom, Hye-Rang; Jang, You-Ran; Altenbach, Susan B.; Vensel, William H.; Simon-Buss, Annamaria; Lim, Sun-Hyung; Kim, Min G.; Lee, Jong-Yeol (Frontiers in Plant Science, 2018)
Wheat gliadins are a complex group of proteins that contribute to the functional properties of wheat flour doughs and contain epitopes that are relevant for celiac disease (CD) and wheat-dependent exercise-induced anaphylaxis (WDEIA). In this study, we extracted ethanol-soluble gliadin fractions from flour of the Korean bread wheat cultivar Keumkang. Proteins were separated by 2-dimensional gel electrophoresis (2-DE) using a pI range of 6 to 11 in the first dimension and subjected to tandem mass spectrometry. α-, γ- and ω-gliadins were identified as the predominant proteins in 31, 28 and one 2-DE spot, respectively. An additional six ω-gliadins were identified in a separate experiment in which a pI range of 3-11 was used for protein separation. We analyzed the composition of CD- and WDEIA-relevant epitopes in the gliadin sequences from Keumkang flour, demonstrating the immunogenic potential of this cultivar. Detailed knowledge about the complement of gliadins accumulated in Keumkang flour provides the background necessary to devise either breeding or biotechnology strategies to improve the functional properties and reduce the adverse health effects of the flour.